Оптимізація інтерактивних вебзастосунків для залученості студентів - Жук, Марія; Морушко, Олександр (Видавництво Львівської політехніки, 2025)
The paper explores the possibility of applying self-determination theory (SDT) and modern UX design principles to optimize interactive web applications in order to improve student engagement in the learning process. The main resource for the developed recommendations is a synthesis of theoretical principles for creating interactive learning environments.
Keywords: інтерактивність; вебзастосунки; залученість студентів; гейміфікація; теорія самодетермінації; соціоніка